Controlling the cell adhesion property of silk films by graft polymerization - Dhyani, Vartika; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report here a graft polymerization method to improve the cell adhesion property of Bombyx mori silk fibroin films. B. mori silk has evolved as a promising material for tissue engineering because of its biocompatibility and biodegradability. However, silk's hydrophobic character makes cell adhesion and proliferation difficult. Also, the lack of sufficient reactive amino acid residues makes biofunctionalization via chemical modification challenging. Our study describes a simple method that provides increased chemical handles for tuning of the surface chemistry of regenerated silk films (SFs), thus allowing manipulation of their bioactivity. By grafting pAAc and pHEMA via plasma etching, we have increased carboxylic acid and hydroxyl groups on silk, respectively. These modifications allowed us to tune the hydrophilicity of SFs and provide functional groups for bioconjugation. Our strategy also allowed us to develop silk-based surface coatings, where spatial control over cell adhesion can be achieved. This control over cell adhesion in a particular region of the SFs is difficult to obtain via existing methods of modifying the silk fibroin instead of the SF surface. Thus, our strategy will be a valuable addition to the toolkit of biofunctionalization for enhancing SFs' tissue engineering applications.
Keywords: Bombyx mori; polymer grafting cell adhesion; silk films